New species of Lachesilla Westwood in the pedicularia group (Psocodea: ’Psocoptera’: Lachesillidae) from the Colombian Amazonia - Manchola, Oscar Fernando Saenz; Aldrete, Alfonso Neri García; Obando, Ranulfo González (Zootaxa, 2015)
Two species of Lachesilla, in the pedicularia species group, from the Colombian Amazonia, are here described and illustrated. Also, a record of L. asymmetriproctus García Aldrete, for the Colombian Department of Putumayo is provided. An identification key to Lachesilla species in the pedicularia group with a single male clunial apophysis is presented, together with a diagnosis of this assemblage of species. A table is included indicating the distribution of Lachesilla species with one and two male clunial apophyses. The species treated in this paper constitute the first lachesillids known from the Department of Putumayo, Colombia.